Answer:
Step-by-step explanation:
Here let's divide both the sides by 3.
Answer:
y=2
Step-by-step explanation:
change y to 2, 6 = 3(2) or 3×2
ln(x + 1) − ln(2) = 1
Answer:
The sollution is x = 2e -1
Step-by-step explanation:
Hi there!!
First, let´s write the equation:
ln(x + 1) - ln(2) = 1
Apply logarithm property: ln(x+1) - ln(2) = ln((x+1)/2)
ln((x+1)/2) = 1
Apply e to both sides of the equation
e^[ln((x+1)/2)] = e¹
Apply e^[ln((x+1)/2)] = (x+1)/2
(x + 1) / 2 = e
Multiply by 2 both sides of the equation
x + 1 = 2e
Substract 1 from both sides of the equation
x = 2e - 1
The sollution is x = 2e -1
Have a nice day!
Answer: m/4
Step-by-step explanation:
M represents the number of children so you would divide them into 4 groups
Show all work?
keep your answer in simplified radical form.
What is the average rate of change from x = 0 to x = 2? (1 point)
−4
−8
1
5
Answer:
It should be the 2nd one
Step-by-step explanation: